Sociological Theory - Adams, Bert N; Sydie,R A (New Delhi Vistar, 2012)
This concise text, covers both classical and contemporary social thought. It traces the major schools of thought over the past 150 years as they appear and reappear in different chapters and looks at important new voices in social theory. The treatment of individual theories and theorists is balanced with the development of key themes and ideas about social life.